2022
DOI: 10.1007/s11356-022-19480-9
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and its influence on renewable energy consumption-environmental performance: the role of ICTs in China

Abstract: Financial inclusion means that individuals and businesses can easily avail financial goods and services at an affordable cost. It is widely recognized that financial inclusion can help preserve the environment by increasing the consumption of renewable energy sources. Hence, our aim is to investigate whether financial inclusion has any effect on renewable energy consumption and environmental quality in China. To get the estimates of the variables, we have preferred the ARDL model. The estimates of the model co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…An increase with 1% will create an increase between 0.05 and 0.16 units in EPI. As many studies (Fotis and Polemis 2018;Khan H. et al, 2021;Musa et al, 2021;Feng et al, 2022) suggest that renewable energy stimulates the reduction of emissions, it means that further the environmental performance could be improved. The practical idea would be that governments should emphasize the need of increasing the share of renewable energy in total energy as it creates less pollution, more reliable solution that mitigates the negative impact on environmental and thus, increases the environmental performance.…”
Section: Panel Data Results and Policy Implicationsmentioning
confidence: 99%
“…An increase with 1% will create an increase between 0.05 and 0.16 units in EPI. As many studies (Fotis and Polemis 2018;Khan H. et al, 2021;Musa et al, 2021;Feng et al, 2022) suggest that renewable energy stimulates the reduction of emissions, it means that further the environmental performance could be improved. The practical idea would be that governments should emphasize the need of increasing the share of renewable energy in total energy as it creates less pollution, more reliable solution that mitigates the negative impact on environmental and thus, increases the environmental performance.…”
Section: Panel Data Results and Policy Implicationsmentioning
confidence: 99%
“…(2022) explored the impact of financial inclusion on China's pollutants and carbon emission from 2011 to 2017 and revealed that increasing financial inclusion can collaboratively decrease pollution and carbon emission. Similarly, Feng et al. (2022) tried to investigate the relationship between financial inclusion and environmental quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The latest study by Shahbaz et al (2022) explored the impact of financial inclusion on China's pollutants and carbon emission from 2011 to 2017 and revealed that increasing financial inclusion can collaboratively decrease pollution and carbon emission. Similarly, Feng et al (2022) tried to investigate the relationship between financial inclusion and environmental quality. Using number of ATMs and insurance policy as a key interest variable and employing the ARDL model study found that an increase in number of ATMs and total insurance enhances the renewable energy consumption and CO 2 emission in China province.…”
Section: Key Literaturementioning
confidence: 99%
“…Financial inclusion is widely acknowledged to benefit the environment by encouraging the use of renewable energy sources (Feng et al, 2022). In China, Feng et al (2022) looked at whether financial inclusion has any impact on renewable energy use and environmental quality.…”
Section: Financial Services As a Means Of Increasing Clean Accessibil...mentioning
confidence: 99%
“…Financial inclusion is widely acknowledged to benefit the environment by encouraging the use of renewable energy sources (Feng et al, 2022). In China, Feng et al (2022) looked at whether financial inclusion has any impact on renewable energy use and environmental quality. The findings revealed that an increase in the number of "ATMs and overall insurance had a long-term favorable impact on renewable energy use in China.…”
Section: Financial Services As a Means Of Increasing Clean Accessibil...mentioning
confidence: 99%